Digital Leadership: Challenges and Opportunities in the Age of Technology : A Literature Review (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
This research aims to analyze the concept of digital leadership, challenges, and opportunities faced by organizational leaders in the technological era. The method used is a literature study with a qualitative approach to explore the definition, characteristics, and strategies of digital leadership. The results showed that digital leadership requires adaptability to technology, data-based decision making, and innovation in managing virtual teams. The main challenges faced are resistance to change and gaps in access to technology, while the main opportunities are the utilization of technologies such as AI and big data.